The Effectiveness of the Quality of Performance Using the Cost Accounting Information System in the Control of Quality Costs Study in the General Company for Electrical Industries (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
The financial operations which carried out by economic unity are proven treatment and documenting and continuous down to makers decision by relevance objective and time and then to reflect on the decision maker in any center of responsibility. That ’s provided by the system accounting information where the source is the basis for producing important accounting information, And the cost accounting information systems of the most important information systems that deal with data processing and conversion to information of relative importance to the beneficiaries. Which is consist with The objective of the research that emphasize the importance of accounting systems in general and systems cost in particular to achieve the highest c The research has led to a number of results, the most important of which is the difficulty in controlling quality costs as well as the waste of economic resources in the company. The researchers recommended adherence to the technical standards to achieve the quality of performance as well as conducting a thorough examination of samples and focusing on the quality of raw materials and testing before use to reduce the proportion Damage.